Obsessive-Compulsive Disorder and Autism Spectrum Disorders: Longitudinal and Offspring Risk - Meier, Sandra M (PLoS One, 2015)
BACKGROUND: Despite substantial similarities and overlaps in the pathophysiology of obsessive-compulsive disorders (OCD) and autism spectrum disorders, little is known about the clinical and etiologic cohesion of these two disorders. We therefore aimed to determine the patterns of comorbidity, longitudinal risks, and shared familial risks between these disorders. METHODS: In a prospective study design we explored the effect of a prior diagnosis of OCD in patients and parents on the susceptibility to autism spectrum disorders and vice versa. Analyses were adjusted for sex, age, calendar year, parental age and place at residence at time of birth. As measures of relative risk incidence rate ratios (IRR) and accompanying 95% confidence intervals (CIs) were employed. RESULTS: The risk of a comorbid diagnosis of OCD in individuals with autism spectrum disorder and aggregation of autism spectrum disorders in offspring of parents with OCD were increased. Individuals first diagnosed with autism spectrum disorders had a 2-fold higher risk of a later diagnosis of OCD (IRR = 2.18, 95% CI = 1.91–2.48), whereas individuals diagnosed with OCD displayed a nearly 4-fold higher risk to be diagnosed with autism spectrum disorders (IRR = 3.91, 95% CI = 3.46–4.40) later in life. The observed associations were somewhat stronger for less severe types of autism spectrum disorders without a comorbid diagnosis of mental disabilities. CONCLUSIONS: The high comorbidity, sequential risk, and shared familial risks between OCD and autism spectrum disorders are suggestive of partially shared etiological mechanisms. The results have implications for current gene-searching efforts and for clinical practice.